Pemanfataan Komputer dan Internet Dalam Pendidikan dan Pembelajaran PAI - Ummu Mawaddah; Ahmadi (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The growing era of digitalization requires that every aspect of life always depends on technology. This advanced technology has contributed greatly to the renewal of various aspects such as business, telecommunications, and even the world of education in particular. Departing from the various facts above, this paper is here to examine more deeply about the use of technology in PAI learning. This study aims to describe : 1) What is the urgency of advances in information technology in the world of education?2) How is the use of computers and the internet in education? 3) How is the use of modern technology through internet-assisted computers in PAI learning? The method used in writing this article is a literature study (library research) by exploring various important information related to the use of computer and internet technology in PAI learning, it can be in the form of books, journal articles, research results, news, reports, and various other important documents that are relevant to this study. Furthermore, after the data has been collected, an inductive analysis is then carried out to then find a relevant and comprehensive conclusion.